2018
DOI: 10.1097/scs.0000000000003408
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Speech Results After Correction of Submucous Cleft Palate With Furlow Palatoplasty and Pharyngeal Flap Combined With Intravelar Veloplasty

Abstract: Submucous cleft palate (SMCP) is a relatively rare variant of the common pathology of cleft palate with specific anatomic and clinical features. Even though there are many surgical options defined previously to correct the SMCP, correction of the velopharyngeal insufficiency and obtaining ideal speech results remains as a challenge. The aim of this article was to compare the speech benefits of Furlow double opposing Z plasty and posterior pharyngeal flap operation combined with intravelar veloplasty for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 16 publications
1
21
0
2
Order By: Relevance
“…Studies only reporting postoperative results were excluded from this table. Despite reporting preoperative nasalance scores, data from Calis et al () were excluded here as results were not independently comparable with other studies—that is, they were reported separately for each syllable and no summative or normative values were included. Phonology and language data reported in Schönweiler et al's () study were also excluded as they were grouped with other forms of orofacial clefting and not specific to SMCP.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies only reporting postoperative results were excluded from this table. Despite reporting preoperative nasalance scores, data from Calis et al () were excluded here as results were not independently comparable with other studies—that is, they were reported separately for each syllable and no summative or normative values were included. Phonology and language data reported in Schönweiler et al's () study were also excluded as they were grouped with other forms of orofacial clefting and not specific to SMCP.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence supporting the impact of surgery type on postoperative speech outcomes was mixed (Afrooz et al, ; Calis et al, ; Ezzat et al, ; Park et al, ). Afrooz et al () and Ezzat et al () reported no significant difference in postoperative velopharyngeal functioning between (a) radical intravelar veloplasty and modified Furlow palatoplasty; and (b) radical intravelar veloplasty and V–Y pushback pharyngoplasty with intravelar veloplasty, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations